(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Computational thinking has regained attention of academicians, politicians and educators in recent years. Stakeholders with different perspectives have considered how to help students develop computational thinking skills. It is important to measure whether a concept, skill or knowledge has been developed or not. The aim of this study is to adapt the computational thinking test developed in Spanish to Turkish. Firstly, computational thinking test was translated into Turkish and evaluated by experts. Secondly, the test was then translated back to Spanish, and the initial version and the back translated version was compared and then the translation process was completed. Lastly, the Turkish version of computational thinking test was administered to middle school students and evaluated for item difficulty, item discrimination and internal consistency. As a result of these analyzes, the test, which had 28 items in Spanish, was reduced to 24 items. The scores obtained from the test were evaluated in terms of gender and grade level. The test scores did not show a statistically significant difference in terms of gender. There was no significant difference in (i) fifth and sixth grade students and (ii) seventh and eighth grade students in terms of students’ computational thinking scores. However, a significant difference was found between these two groups (5-6 and 7-8). Computational thinking test can be used by researchers and educators in their studies and for their teaching.